Baju Adat Lipaq Saqbe: Warisan Budaya yang Memperkuat Identitas Sosial Suku Mandar - Isnaini Putri Az-Zahra; Syairul Bahar; Meicca Javanisa Utami; Mutiara Cinta; Mutiara Cinta4, Naila Azzahra; Muhammad Fattan Fachrezy; Farkhan Abdurochim Alfarauq (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the symbolic meaning of Lipaq Saqbe as a social identity of the Mandar Tribe. This traditional clothing not only functions as a cultural identity but also has a deep symbolic meaning and reflects the values ​​of the Mandar people. This study uses qualitative descriptive methods and Malinowski's functionalist theory to understand the social and cultural functions of Lipaq Saqbe clothing. The results of the study indicate that the motifs and colors of Lipaq Saqbe have certain meanings related to social status and personal identity. In addition, the use of this traditional clothing in various traditional ceremonies shows its important role in preserving culture. The Mandar Tribe has adapted to the development of the times while maintaining the authenticity of its traditional motifs, making Lipaq Saqbe a symbol of their living cultural heritage. This study is expected to contribute to the understanding of socio-cultural dynamics in Indonesia, especially in West Sulawesi.